Phononic heat transfer through a one dimensional system subject to two sources of nonequilibrium - Beraha, Natalia (2015)
We analyze the energy transport in a one dimensional chain composed by two Frenkel-Kontorova (FK) segments connected together by a time modulated coupling. The ends are immersed in two thermal reservoirs with oscillating temperatures. We observe a single and multiresonant heat transport depending on the regimes considered, with a crossover between a mechanical resonance and a thermodynamical resonance. The dynamical tuning between these two regimes requires the synergetic presence of both time dependent sources of nonequilibrium. In the single resonant regime we analyze a "red shifted" resonant frequency that is dependent on the size of the system.